2000
DOI: 10.1021/jm990467o
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships and Binding Mode of Styrylquinolines as Potent Inhibitors of HIV-1 Integrase and Replication of HIV-1 in Cell Culture

Abstract: Our prior studies showed that polyhydroxylated styrylquinolines are potent HIV-1 integrase (IN) inhibitors that block the replication of HIV-1 in cell culture at nontoxic concentrations. To explore the mechanism of action of these inhibitors, various novel styrylquinoline derivatives were synthesized and tested against HIV-1 IN and in cell-based assays. Regarding the in vitro experiments, the structural requirements for biological activity are a carboxyl group at C-7, a hydroxyl group at C-8 in the quinoline s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
113
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 31 publications
8
113
0
2
Order By: Relevance
“…As shown in docking results, the oxygen atoms of carboxyl group and hydroxyl group may coordinate with Mg +2 ion within the enzyme catalytic site. 39 This docking mode was the same as the experiment report given by zouhiri et al 34 Thus, based on previous studies the oxygen atoms of carboxyl group and hydroxyl group in styrylquinolines have dominant role in drug activity regardless of determining the active sites.…”
Section: From Expresionmentioning
confidence: 67%
See 2 more Smart Citations
“…As shown in docking results, the oxygen atoms of carboxyl group and hydroxyl group may coordinate with Mg +2 ion within the enzyme catalytic site. 39 This docking mode was the same as the experiment report given by zouhiri et al 34 Thus, based on previous studies the oxygen atoms of carboxyl group and hydroxyl group in styrylquinolines have dominant role in drug activity regardless of determining the active sites.…”
Section: From Expresionmentioning
confidence: 67%
“…Some previous researches 34 indicate that the presence of a 7-carboxyl-8-hydroxyl patterns in the quinoline half and an aromatic or heteroaromatic ancillary subunit is required for the biological activity of styrylquinoline (Figure 1).…”
Section: From Expresionmentioning
confidence: 96%
See 1 more Smart Citation
“…The antibacterial activity of 8-hydroxyquinoline and its derivatives is long-known. The drugs from this group are used as chemotherapeutics in medicine for more than 120 years (9,10,11,21), and in analytical chemistry as chelators (8,12). In previous studies of ours, some newly synthesized derivatives of 8-Quinolinol were shown to exhibit a higher microbiological activity (4,5,15).…”
Section: Introductionmentioning
confidence: 92%
“…The Quantitative Structure Activity Relationship (QSAR) approach is widely used to look for and predict new compounds with high biological activity. The evaluation of the bioactivity of such compounds through their physical, chemical and physicochemical traits is most commonly performed with regression equations of the structure-activity type using regression analysis (6,7,14,21). The purpose of this method is to derive empirical relations between various sets of chemical, physical or structural parameters and the biological activity of compounds.…”
Section: Introductionmentioning
confidence: 99%